Análise das variáveis temporais da marcha de idosos com e sem doença de Parkinson em simulação de travessia de rua - Oliveira, Lucyana Teodoro (2018)
The identification of risk factors for falls and traffic accidents in elderly pedestrians with and without Parkinson's disease (PD) is a strategy to reduce public spending and provide greater functional independence and better quality of life for this group. This study's aim was to evaluate changes in the gait of the elderly with and without PD during street crossing simulation through temporal and kinematic parameters. The study included 40 elderly people aged between 60 and 80 years old, 20 of them with PD and 20 without PD. The street crossing simulations occurred in 3 conditions: normal gait (condition 1), gait during street crossing simulation (condition 2), and gait during street crossing simulation with reduced time (condition 3). Foot Switch sensors were used to collect data. The data analysis was performed by the Noraxon ® program over participants' 10 gait cycles. The results showed that the elderly with and without PD had longer step and stride times in condition 1 than in conditions 2 and 3. In the comparison between groups, the elderly with PD had longer support time and shorter swing time during conditions 1 and 2 than the elderly without PD. When in street crossing situations, the elderly with and without PD are able to make changes in the temporal parameters, such as decreasing step and stride times, in order to complete the tasks imposed. Our study can be used in combination with future research, in order to create strategies to make public roads safer for people with PD and reduce public spending.